Association of immune-related adverse events with the outcomes of immune checkpoint inhibitors in patients with dMMR/MSI-H metastatic colorectal cancer - Chiara Cremolini; Sara Lonardi; Filippo Pietrantonio; Francesca Corti; Elisabetta Fenocchio; Massimiliano Salati; Margherita Ambrosini; Michael J Overman; Lisa Salvatore; Rossana Intini; Priya Jayachandran; Javier Ros; et al. (Journal for ImmunoTherapy of Cancer)
Background Immune checkpoint inhibitors (ICIs) show a tremendous activity in microsatellite instability-high (MSI-H) metastatic colorectal cancer (mCRC), but a consistent fraction of patients does not respond. Prognostic/predictive markers are needed. Despite previous investigations in other tumor types, immune-related adverse events (irAEs) have not been well evaluated in patients with MSI-H cancers treated with ICIs.Methods We conducted an international cohort study at tertiary cancer centers collecting clinic-pathological features from 331 patients with MSI-H mCRC treated with ICIs. Of note, the irAEs were summarized using a ‘burden score’ constructed in a way that the same score value could be obtained by cumulating many low-grade irAEs or few high-grade irAEs; as a result, the lower the burden the better. Clearly, the irAE burden is not a baseline information, thus it was modeled as a time-dependent variable in univariable and multivariable Cox models.Results Among 331 patients, irAEs were reported in 144 (43.5%) patients. After a median follow-up time of 29.7 months, patients with higher burden of skin, endocrine and musculoskeletal irAEs (the latter two’s effect was confirmed at multivariable analysis) had longer overall survival (OS), as opposed to gastrointestinal, pneumonitis, neurological, liver, renal and other irAEs, which showed an harmful effect. Similar results were observed for progression-free survival (PFS). Based on the results retrieved from organ-specific irAEs, ‘aggregated’ burden scores were developed to distinguish ‘protective’ (endocrine and musculoskeletal) and ‘harmful’ (gastrointestinal, pneumonitis, neurological, hepatic) irAEs showing prognostic effects on OS and PFS.Conclusions Our results demonstrate that not all irAEs could exert a protective effect on oncologic outcome. An easy-to-use model for ICIs toxicity (burden score of protective and harmful irAEs) may be used as surrogate marker of response.